Effect of a Food Scholarship Program on Food Security Status and Diet Quality of College Students (P04-069-19). (13th June 2019) - Moore, Carolyn; Alexis, Torrey; Dave, Jayna; Miketinas, Derek; Chen, Tzu-An
Abstract: Objectives: To determine how food insecurity is associated with overall diet quality in college students following the implementation of a new food scholarship program. Changes of Healthy Eating Index (HEI) and food security status were compared over a 10-week period. Methods: A new food scholarship program at Texas Woman's University in Houston provided students fresh fruits and vegetables, dairy and meat products, as well as non-perishable foods twice monthly. The Houston Food Bank donated all foods. Baseline and 10-week data were collected. Food security was measured with the USDA 6-item short form of the Food Security Survey Module. Total HEI-2015 and component scores were calculated from analysis of 3-day food records and compared by paired t-tests. ANCOVA estimated the impact of food security (high, low, very low) on HEI post scores, controlling for HEI baseline scores, age, gender, and race. Results: Participants ( n  = 49) were primarily female ( n  = 38, 78%) with an average age of 28 ± 8 years. Ethnic/race distribution was 49% White, 27% Asian, 20% Black, and 4% other. Participants were primarily single (76%). Food security was low (31.9%) or very low (19.1%) at baseline; at post-test, participants reporting very low food secure dropped to 15.6%. Total HEI-2015 scores at baseline (55.9 ± 11.54) did not increase significantly after 10 weeks (57.7 ± 10.63) ( P  = 0.298). However, after 10 weeks, total vegetable scores significantly increased (2.64 ± 1.39 to 3.19 ± 1.33) ( P  = 0.023). There was no significant food security group effect ( P  = 0.49); however, there was a positive association between age and HEI post scores independent of the other model effects (β = 0.59 +  0.17; P  = 0.001). Conclusions: HEI-2015 total vegetable component scores increased with implementation of a food scholarship program. Nevertheless, many college students remained food insecure and overall diet quality needs improvement. Funding Sources: Food donated by the Houston Food Bank.